Tortoises, hares, and vaccines: A cautionary note for SARS-CoV-2 vaccine development - Poland, Gregory A. (Vaccine, 2020)
[...]RNA viruses accumulate mutations that can sometimes circumvent vaccine-induced immunity. [...]issues of broad immunogenicity exist. Who should be included—perhaps healthcare providers and first responders who share the highest risk of infection as a starting point? –What, if any, animal models might be developed that allow the “animal rule” to be utilized in an effort to accelerate research and licensure? –If phase I and II trials are conducted earlier than normal procedure, could a phased initiation of studies from highest risk to lowest risk subjects be utilized? –Might one conceive of differential regulatory pathways for vaccine candidates using well-understood antigens, vaccine methodology, adjuvants, manufacture, and routes of administration (TBD) versus those using novel delivery technology and novel antigens or adjuvants? –As mentioned above, human challenge studies have been advanced as a method to rapidly determine efficacy in discussions I have had with other vaccinologists.